When switching costs cause market power: Rubber processing in Indonesia - Thomas Kopp (Agricultural Economics, 2021)
Suppliers of agricultural output incur switching costs (SCs) when choosing new buyers, allowing buyers to exercise oligopsonistic market power, as SCs help buyers to mark down prices for incumbent suppliers. This article conceptualizes the idea of SCs and suggests an empirical strategy for quantifying them through an estimation of farm supply to specific buyers. The model incorporates price differences between buyers, revealing buyers' anticipations of suppliers' SCs. The approach is applied to the Indonesian rubber market, employing a data set of daily purchasing prices and less frequent quantities of individual sales instances. Results indicate that SCs exist and are at about 3% of the farm gate price, leading to substantial redistribution from suppliers to buyers of agricultural~output.
Keywords: 330; Bertrand paradox; law of one price; oligopsony; rubber; switching costs; value chain analysis